1994
DOI: 10.1213/00000539-199402000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Hemodynamics and Histamine Release of Rocuronium (Org 9426) When Administered in Increased Doses Under N[2]O/O[2]-Sufentanil Anesthesia

Abstract: The cardiovascular effects, histamine release potential, and pharmacodynamics of rocuronium were determined in adult patients randomized to receive rapid (5 s) intravenous (i.v.) bolus doses of 600, 900, or 1200 micrograms/kg (2.0, 3.0, and 4.0 times the ED95) with maintenance doses of 150 micrograms/kg. There were no statistically significant hemodynamic effects (heart rate, blood pressure, mean arterial pressure [MAP] or electrocardiogram [ECG]) after administration of rocuronium. There were no increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 0 publications
5
20
0
2
Order By: Relevance
“…7 However, the small sample size probably accounts for the lack of statistical significance in these observations. As did Levy et al, 9 we observed an absence of histamine-related symptoms. Eleven of the 20 study subjects were receiving beta-blockers and/or calcium channel blockers before surgery.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…7 However, the small sample size probably accounts for the lack of statistical significance in these observations. As did Levy et al, 9 we observed an absence of histamine-related symptoms. Eleven of the 20 study subjects were receiving beta-blockers and/or calcium channel blockers before surgery.…”
Section: Discussionsupporting
confidence: 88%
“…6 In contrast, Cornet et al showed no change in HR, MAP, PCWP, or CI and no ischaemic episodes as evaluated by computerised ST-segment analysis and TEE evaluation of left ventricular function in patients mainrained with rocuroninm undergoing abdominal aortic surgery, s These findings were similar to the findings of Levy et aL, which showed no alteration in HR, BP, MAP, or ECG after rocuronium in adult patients during nitrous oxide/oxygen-sufentanil Anaesthesia. 9 Decreases in CVP and MPAP were observed in the present study, suggesting that rocuronium has systemic venodilatory effects. The PVfk was not augmented, and no other haemodynamic change was noted in the grouped data.…”
Section: Discussionsupporting
confidence: 62%
“…10 Levy et al investigated the haemodynamic effects of 0.6, 0.9 or 1.2 mg/kg Rocuronium (2, 3 and 4 X ED95). 11 The cardiovascular profile of the three increasing doses was similar and none of the three doses had any adverse effect on the cardiovascular functions of any patients. 11 Nitschmann using rocuronium (0.9 mg/kg) or Vecuronium (0.15 mg/kg) in patients undergoing coronary artery bypass grafting reported no significant change in haemodynamics.…”
Section: Discussionmentioning
confidence: 80%
“…All the values between the two groups are non-significant when compared and our findings in the present study were in accordance with McCoy et al, Levy et al and Nitschmann et al which was found no significant alteration in haemodynamics after Rocuronium administration. [10][11][12] McCoy et al used invasive cardiovascular monitoring studied the cardiovascular effects of Rocuronium in humans. There was no evidence of histamine release in any patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rocuronium, the most commonly used muscle relaxant in anesthesia today, is associated with a significant incidence of anaphylaxis during anesthesia but has not yet been categorized as an initiator in mastocytosis [50]. In a manufacturer-sponsored, prospective, randomized clinical trial, rocuronium up to 1.2 mg/kg IV was administered to 45 adult patients under N 2 O/O 2 -sufentanil anesthesia and plasma histamine levels were not found to be significantly increased [71]. Rocuronium has, however, been associated with increased intradermal histamine levels by use of a microdialysis technique [65].…”
Section: Intraoperative Managementmentioning
confidence: 99%